From Landfill to Loom: Two Teacher-Researchers Chronicle Their Sustainability Narratives via The Secret Under My Skin - Morawski, Cynthia Marlene; Dunnington, Catherine-Laura (Journal of the Canadian Association for Curriculum Studies, 2020)
Traditionally, the responsibility for sustainability education has been assigned to the fields of science, engineering, technology and outdoor education. More recently, English language arts have begun to play an integral role in educating students on the importance of preserving the environment for future generations. Pertinent research, however, indicates that many teachers, including those teaching English, do not feel fully prepared to address sustainability in their classrooms. Such teachers would benefit from either pre-service or in-service support where they would have opportunities to gain more knowledge about sustainability, while also critically inquiring into their related pedagogical beliefs and practices. Before beginning the process of planning and implementing relevant sustainability education experiences for English teachers, it is imperative that we, two teacher educators, first examine our own teaching narratives related to this important topic. Focusing on the dystopian young adult novel, The Secret Under My Skin (McNaughton, 2000), we make generous use of Rosenblatt’s (1995) transactional theory of reader response to critically inquire into past experiences that shape our recurrent views and actions in the classroom. We express our back-and-forth transactions in interspersing sections of poetry, prose and image, including emerging questions to consider as starting points for future engagement with teachers on the integration of sustainability education into the English language arts curriculum at the secondary school level.